Environmental Stratified Flows - Grimshaw, Roger. (Topics in Environmental Fluid Mechanics, 2002)
The dynamics of flows in density-stratified fluids has been and remains now an important topic for scientific enquiry. Such flows arise in many contexts, ranging from industrial settings to the oceanic and atmospheric environments. It is the latter topic which is the focus of this book. Both the ocean and atmosphere are characterised by the basic vertical density stratification, and this feature can affect the dynamics on all scales ranging from the micro-scale to the planetary scale. The aim of this book is to provide a ỚSstate-of-the-artỚ<U+00fd> account of stratified flows as they are relevant to the ocean and atmosphere with a primary focus on meso-scale phenomena; that is, on phenomena whose time and space scales are such that the density stratification is a dominant effect, so that frictional and diffusive effects on the one hand and the effects of the earthỚ"s rotation on the other hand can be regarded as of less importance. This in turn leads to an emphasis on internal waves.